2019
DOI: 10.14778/3372716.3372728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating persistent memory range indexes

Abstract: Persistent memory (PM) is fundamentally changing the way database index structures are built by enabling persistence, high performance, and (near) instant recovery all on the memory bus. Prior work has proposed many techniques to tailor index structure designs for PM, but they were mostly based on volatile DRAM with simulation due to the lack of real PM hardware. Until today is it unclear how these techniques will actually perform on real PM hardware. With the recent released Intel Optan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 24 publications
6
28
2
Order By: Relevance
“…We have experimented with varying block sizes as well as degrees of parallelism (i.e., threads and I/O depth) and report the best throughput. The measurements are largely in accordance with the specifications and other reports [9,11,18,32,38]. One anomaly, however, is the sequential write bandwidth for DRAM, which should be closer to the read speed.…”
Section: Persistent Memorysupporting
confidence: 88%
See 1 more Smart Citation
“…We have experimented with varying block sizes as well as degrees of parallelism (i.e., threads and I/O depth) and report the best throughput. The measurements are largely in accordance with the specifications and other reports [9,11,18,32,38]. One anomaly, however, is the sequential write bandwidth for DRAM, which should be closer to the read speed.…”
Section: Persistent Memorysupporting
confidence: 88%
“…They propose a persistent linked list of leaf nodes while keeping the inner nodes in DRAM, which are rebuilt upon recovery. Evaluations on real hardware have already shown that this division is definitely practical for hiding PMem's higher latency and achieving DRAM-like performance [18]. With the LB + -Tree [22] the authors refine the concept for Intel's DCPMMs by utilizing multi-256-byte nodes and limiting the number of PMem line writes.…”
Section: Multi-level Data Structuresmentioning
confidence: 99%
“…We observe that Px86's asynchronous explicit persist instructions lie in sharp contrast with a variety of previous work and developers' guides, ranging from theory to practice, that assumed, sometimes implicitly, łsynchronousž explicit persist instructions that allow the programmer to assert that certain write must have persisted at certain program points (e.g., [Arulraj et al 2018;Chen and Jin 2015;David et al 2018;Friedman et al 2020Friedman et al , 2018Gogte et al 2018;Izraelevitz et al 2016b;Kolli et al 2017Kolli et al , 2016Lersch et al 2019;Liu et al 2020;Oukid et al 2016;Scargall 2020;Venkataraman et al 2011;Yang et al 2015;Zuriel et al 2019]). For example, Izraelevitz et al [2016b]'s psync instruction blocks until all previous explicit persist institutions łhave actually reached persistent memoryž, but such instruction cannot be implemented in Px86.…”
Section: Introductioncontrasting
confidence: 69%
“…Still, a combination of both seems promising. Since former experiments work on emulated PMem, in [22], the authors re-evaluated the B + -Tree variants on real hardware. In [10,11], the underlying primitives of these trees are also analyzed on real PMem.…”
Section: Related Workmentioning
confidence: 99%